1996
DOI: 10.1063/1.360954
|View full text |Cite
|
Sign up to set email alerts
|

Alloy nonrandomness in diluted magnetic semiconductors

Abstract: A simple model of alloy nonrandomness is introduced within a framework where the effective concentration of spin singlets as a function of the nominal concentration of magnetic ions in a nonrandom alloy can be obtained by transformations of the corresponding function in random alloys. The theory shows that a given system that is appreciably nonrandom can have a magnetic response almost identical with that of a random distribution. Possible ways of identifying alloy nonrandomness in diluted magnetic semiconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Harrison et al 108 questioned the sensitivity of this technique for detecting a nonrandom distribution, using the fcc cation lattice as an example. However, their conclusion is based on invalid approximations.…”
Section: E Nonrandom Distribution Of Magnetic Ions In Bulk Dmssmentioning
confidence: 99%
“…Harrison et al 108 questioned the sensitivity of this technique for detecting a nonrandom distribution, using the fcc cation lattice as an example. However, their conclusion is based on invalid approximations.…”
Section: E Nonrandom Distribution Of Magnetic Ions In Bulk Dmssmentioning
confidence: 99%
“…However, recently we have pointed out some of the possible consequences of a nonrandom distribution of the magnetic ions. 3,9 In particular, we have shown that alloy clustering can give rise to one of several effects which are dependent on the nominal concentration x of the Mn ions. This arises from the fact that, relative to a random distribution, the effect of clustering is to give rise to regions in which x is increased and to other regions where x is decreased.…”
Section: Introductionmentioning
confidence: 96%
“…In the case of Zn Mn Se it is [18], [19] eV so the -potential is given by meV (24) As the barrier thickness decreases, interactions among the wells become stronger so the splitting becomes larger. Additionally, the spin splitting is increased because the antiferromagnetic interactions between magnetic ions are reduced which leads to significantly enhanced effective magnetic moments and thepotential [18], [19], [22], [23]. The thickness of magnetic barriers was here set to 1 nm, in the range considered in the literature [18], [19].…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…It takes into account the effect of graded interfaces, the interface roughness and the enhanced magnetization at interfaces. Since the parameters used for the characterization of the interface profile are not known for ZnMnSe-ZnCdSe-ZnSe systems, we used a modified model [22], [23] that introduces a 2-monolayer-wide intermixing region left and right of the DMS barrier assuming different Mn concentrations, effective Mn concentrations and effective temperatures in the barriers and the intermixing regions. The complete potential profile of a triple quantum-well structure including the intermixing regions represented by dashed lines is shown in Fig.…”
Section: Theoretical Modelmentioning
confidence: 99%